International commercial agreements and electronic commerce - Fox, William F. (Kluwer Law International B. V., 2018)
"[This book] provides guidance on drafting and negotiating international business contracts and resolving contractual disputes, including contracts formed by electronic commerce. Although negotiation still lies at the heart of international commercial agreements, much of the drafting and other details have migrated to the Internet where most of the work is done electronically. This...one-volume work now in its sixth edition with its deeply informed emphasis on both the face-to-face and electronic components of setting up, negotiating, and implementing an international commercial agreement stands alone among contract drafting guides and proves its enduring worth."--